Corrigendum: Analysis of Eco-Enzyme Potential to Reduce BOD, COD, Oil and Grease Concentrations in Raw Water for Treated Water in Karawang: A Laboratory Experiment - Gina Lova Sari; Wilma Nurrul Adzillah; Kania Ratnawati; Devita Fitria Alam Sari; Saidah Saidah (Gema Lingkungan Kesehatan, 2026)
This corrigendum is issued to correct several editorial and typographical errors in the article entitled "Analysis of Eco-Enzyme Potential to Reduce BOD, COD, Oil and Grease Concentrations in Raw Water for Treated Water in Karawang: A Laboratory Experiment", published in Gema Lingkungan Kesehatan, Volume 23, Issue 1, 2025 (DOI: https://doi.org/10.36568/gelinkes.v23i1.148). The corrections include: (1) capitalization and typographical revisions, (2) correction of the technical term "treated", (3) correction of the composition value for Variation D in Table 2 from 2,750.00 : 150.00 to 2,750.00 : 250.00 (Raw Water : Eco-Enzyme), and (4) replacement of several figure and graph labels from Indonesian to English. The correction to Table 2 reflects the actual experimental composition used throughout the study and resulted from a transcription error during the final manuscript preparation. These corrections do not affect the research methodology, experimental procedures, data analysis, results, discussion, scientific interpretation, or conclusions of the published article. This corrigendum is published to ensure the accuracy, clarity, and integrity of the scientific record.